DIVERSE LITERARY WORKS IN GLOBAL LINGUISTIC CONTEXTS - Rustamov Ilkhom Tursunovich (TADQIQOTLAR.UZ, 2024)
Abstract: This article delves into the importance of varied literary compositions within the paradigm of global linguistic environments. It scrutinizes the manner in which literature originating from diverse linguistic origins enhances cultural interchange, comprehension, and admiration. By conducting a thorough examination of pertinent scholarly materials and critical discussions, this research endeavors to explore how a multitude of literary works from different linguistic backgrounds enhances the overall richness of the global literary sphere.